A customized sinistra ocular prosthesis for a geriatric patient - Dian Samuel Hasudungan; Haryo Mustiko Dipoyono; Intan Ruspita; Sri Budi Barunawati (Indonesian Journal of Prosthodontic, 2023)
Geriatric patients have limitations such as lack of communication, finance, and limited visit time. Therefore, fabrica-ted ocular prosthesis is preferred. On the other hand, fabricated ocular prosthesis have disadvantage of not being able to fit completely in the eye socket. To overcome this problem, the patients need an appropriate prosthesis to in-crease their quality of life. A 75-year-old male patient, came to RSGM UGM Prof. Soedomo, using fabricated ocular prosthesis, complained that his ocular prosthesis loose and there was discoloration. Clinical examination, there were no abnormalities in the eye socket. The treatment plan was making customized ocular prosthesis using acrylic resin. The treatment procedure comprises impressing the eye by using individual tray; making the model of wax sclera followed by trying on the wax sclera pattern to the patient eye socket and continuing the acrylic resin process of scle-ra followed by trying to the eye socket, and then determining the location and iris diameter to draw the iris and pupil. The final process is by inserting the ocular prosthesis to the patient eye socket. One week after insertion, the patient felt comfortable and had no complaints. Ocular prosthesis helps to improve the patient’s quality of life.